Selection of Key Performance Indicators and Performance of Water Projects in Machakos County, Kenya - Richard Orengo Odhiambo; Charles M. Rambo; Catherine W. Ngahu (STIE Malangkucecwara, 2026)
Access to sustainable, clean, and safe water remains a central development priority, and improving the performance of water projects is critical in achieving this goal. This study assessed the influence of the selection of key performance indicators (KPIs) on the performance of water projects in Machakos county, Kenya. Guided by a pragmatism paradigm, the study adopted a correlational and descriptive cross-sectional design. The target population comprised 70 water projects, with 216 respondents selected through stratified random sampling, including project managers, Ministry of Water employees, and water management committee members. Data were collected using semi-structured questionnaires, key informant interviews, and secondary reports. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative data were analyzed thematically. Correlation results revealed a positive and significant relationship between KPI selection and project performance (r= 0.225, p= 0.005), while regression analysis confirmed that KPI selection positively influences performance (β= 0.395, p= 0.005). These findings imply that participatory selection of specific, measurable, realistic, relevant, and time-bound KPIs enhances accountability, resource allocation, and project outcomes. The study contributes to performance management literature in developingcountry contexts and provides practical insights for policymakers and project managers on strengthening results-based monitoring frameworks.